2009
DOI: 10.1051/alr/2009047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, stocking density and farming conditions on fin damage in European sea bass (Dicentrarchuslabrax)

Abstract: -This paper presents a non invasive, rapid and reliable way to quantitatively assess fin erosion in sea bass (Dicentrarchus labrax). The method is based on a visual assessment of fin profile and area loss of all fins except the anterior dorsal, on a scale from 0 to 4 in comparison with a perfect fin. The effects of stocking density (SD) and temperature on fin damage were investigated under experimental conditions (100-250 g fish). Over a 4-month period, mean erosion index (mean erosion level of all fins) was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Damaged fin condition is a regular phenomenon associated with intensive fish farming (Latremouille, ). It has been recorded, for example, in rainbow trout ( Oncorhynchus mykiss ; St‐Hilaire et al., ; Ellis et al., ), salmon ( Salmo salar ; Jones et al., ), perch (Stejskal et al., ), sea bass ( Dicentrarchus labrax ; Person‐Le Ruyet and Le Bayon, ), cod ( Gadus morhua ; Hatlen et al., ), and many others, and is usually a result of bacterial infection and/or aggressive behaviour of fish cultured at high densities (e.g. Jobling et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Damaged fin condition is a regular phenomenon associated with intensive fish farming (Latremouille, ). It has been recorded, for example, in rainbow trout ( Oncorhynchus mykiss ; St‐Hilaire et al., ; Ellis et al., ), salmon ( Salmo salar ; Jones et al., ), perch (Stejskal et al., ), sea bass ( Dicentrarchus labrax ; Person‐Le Ruyet and Le Bayon, ), cod ( Gadus morhua ; Hatlen et al., ), and many others, and is usually a result of bacterial infection and/or aggressive behaviour of fish cultured at high densities (e.g. Jobling et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Each individual was measured for length and photographed with a tripod‐mounted digital camera with a light source. Fin erosion was determined for all fins according to the fin erosion scale of Person‐Le Ruyet and Le Bayon (), which quantifies the progressive loss in fin area of seabass ( D. labrax ) juveniles and adults. This index is a numerical system based on a visual assessment of fin condition of all fins on a scale from 0 (perfect fin) to 4 (short and dysfunctional fin).…”
Section: Methodsmentioning
confidence: 99%
“…This index is a numerical system based on a visual assessment of fin condition of all fins on a scale from 0 (perfect fin) to 4 (short and dysfunctional fin). The anterior dorsal fin area of both seabream ( S. aurata ) and seabass ( D. labrax ) were excluded from erosion assessment because they are usually damaged by handling and therefore difficult to assess (Person‐Le Ruyet and Le Bayon, ). The erosion parameters were calculated from erosion levels of all fins as follows: Fin Erosion Index (FEI), erosion level mean of the five fins and each fin separately of all fish sampled per fish origin; Fin Splitting Index (FSI), mean number of splits per fish calculated for all fins and specific fins separately of all fish sampled per fish origin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant body of experimental research which identified that the main factors affecting fin damage are feeding practices, water quality, stocking density and routine handling, not excluding the bacterial infections (3,6,7,8,9). However, despite the experimental approach, there are few research reports that determine the important factors having effect on fin damage and fish welfare under different commercial production systems (5,10).…”
Section: Introductionmentioning
confidence: 99%